Morphogenesis and classification of corrosion plains in Slovenia - Stepišnik, Uroš; Ferk, Mateja (Acta geographica Slovenica, 2024)
A new study of corrosion plains in Slovenia provides a systematic classification based on their geological settings and morphology. They are grouped into four types: karst plains, dry poljes, marginal plains of contact karst, and marginal plains of fluviokarst. Karst plains are the largest, formed through denudation under stable tectonic and hydrogeological conditions. Dry poljes are closed basins composed of bedrock and scattered sediment. Marginal plains of contact karst are formed at the boundary between non-karst and karst environments, while marginal plains of fluviokarst result from multiphase formation of poljes due to tectonic activity. This study enhances understanding of corrosion plains and can assist in their identification and management in karst areas.